Persistent organic pollutants in meat, liver, tallow and bone marrow from semi-domesticated reindeer (Rangifer tarandus tarandus L.) in Northern Norway - Hassan, Ammar Ali; Rylander, Charlotta; Brustad, Magritt; Sandanger, Torkjel Manning (Acta Veterinaria Scandinavica, 2013)
Background: The aim of this project was to study 14 polychlorinated biphenyls (PCBs), 5 dichlorodiphenyl trichloroethans (DDTs), 12 organochlorine pesticides (OCPs) and 6 polybrominated diphenylethers (PBDEs) in meat, liver, tallow and bone marrow from semi-domesticated reindeer. Methods: Meat, liver, tallow, and bone marrow samples (n= 30) were collected from semi-domesticated reindeer in Northern Norway. Determination of the persistent organic pollutants (POPs) concentrations was done by using gas chromatography–mass spectrometry (GC-MS). Dependent sample t-test and Pearson’s correlation test were used in statistical analysis. Results: Concentrations of the persistent organic pollutants in the samples from semi-domesticated reindeer were generally low and slightly above the limit of detection (LOD). For PCBs and OCPs, ≥ 50% of the samples had concentrations above LOD. For the DDTs and PBDEs, the proportion of samples with concentrations above LOD varied between 3.7 and 45.5% depending on the sample type. Concentrations of PCB 99, 105, 138/163, 153 and 187 differed significantly between meat and liver, whereas concentrations of PCB 183 were significantly different between tallow and bone marrow. Furthermore, concentrations of hexachlorobenzene (HCB) were significantly different between meat and liver. Significant correlations were revealed in concentrations of 5 PCB congeners between the studied tissue types. Conclusion: Concentrations of the POPs revealed in this study were generally low.